2018
DOI: 10.32890/mjli2017.14.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metalanguage Among Second Language Learners to Mediate L2 Grammar Learning

Abstract: Purpose-This study investigated the use of metalanguage as a mediational tool in understanding targeted grammatical concepts from the perspective of the Sociocultural approach (SCT) in learning a second language (L2). Methodology-The participants involved in this study were Malay undergraduates with low to intermediate proficiency in L2 English. The protocols of learners' verbalisation during a Concept-Based Instruction (CBI) language task were analysed to explore how learners used metalanguage to mediate, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
2
Order By: Relevance
“…These results fit with the common belief that explicit grammatical instruction involving a clear explanation of terms would help develop students' grammatical accuracy. In this vein, researchers provided various justifications, such as providing more effective ways for learning the language (Schleppegrell, 2013), developing learner autonomy (Ellis, 2016), and supporting learners' cognitive development (Harun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results fit with the common belief that explicit grammatical instruction involving a clear explanation of terms would help develop students' grammatical accuracy. In this vein, researchers provided various justifications, such as providing more effective ways for learning the language (Schleppegrell, 2013), developing learner autonomy (Ellis, 2016), and supporting learners' cognitive development (Harun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A commonly asked question about grammar instruction is whether to teach it explicitly or implicitly (Harun et al, 2017). Both methods have undergone assessment and analysis, creating a heavy debate on grammar teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“…En su estudio Harun et al (2017), investigó el uso del metalenguaje como herramienta de mediación en la comprensión de conceptos gramaticales específicos desde la perspectiva del enfoque sociocultural (SCT, The SocioCultural Theory por sus siglas en inglés) en el aprendizaje de una segunda lengua (L2). Como Harun et al (2017), Naqvi et al (2010), en su estudio asociaron la conciencia metalingüística con la teoría sociocultural en un aula para promover el aprendizaje a través de la cooperación y la interacción. Ambas investigaciones inquieren en el impacto de la perspectiva sociocultural en contextos educativos de L2 que promueven el desarrollo de la conciencia metalingüística.…”
Section: Marco Teórico 21 Conciencia Metalingüística Enmarcada En Ununclassified
“…Para concluir, estos enfoques de métodos mixtos requieren un análisis microgenético cualitativo del discurso de los estudiantes (Harun et al 2017;Naqvi et al 2010;Sampson, 2019) que describe en detalle cómo los estudiantes generan conocimiento sobre estructuras gramaticales que causan problemas en L2.…”
Section: Marco Teórico 21 Conciencia Metalingüística Enmarcada En Ununclassified
“…Findings showed that mediating artifacts (e.g., written concept explanations and pedagogical diagrams) and collaborative activities (e.g., verbalized refection and self-directed speech) are all effective ways to mediate learners' L2 learning. Harun and Abdullah (2017) [24] focused on how metalanguage was used as a mediating tool by the learners in understanding targeted grammatical concepts. The protocols of learners' verbalisation during a CBI language task were analysed by Languaging Units identification.…”
Section: Current Progress Of International Researchmentioning
confidence: 99%